Hydrogen Oxidation Pathway Over Ni–Ceria Electrode: Combined Study of DFT and Experiment - Jiang, Yunan; Wang, Shuang; Xu, Jun; Zheng, Minghao; Yang, Yi; Wu, Xiaojun; Xia, Changrong (Frontiers in Chemistry, 2021)
Ni-ceria cermets are potential anodes for intermediate-temperature solid oxide fuel cells, thanks to the catalytic activity and mixed conductivities of ceria based materials associated with the variable valence states of cerium. However, the anodic reaction mechanism in the Ni-ceria systems needs to be further revealed. Via density functional theory with strong correlated correction method, this work gains insight into reaction pathways of hydrogen oxidation on a model system of Ni10-CeO2(111). The calculation shows that electrons tend to be transferred from Ni10 cluster to cerium surface, creating surface oxygen vacancies. Six pathways are proposed considering different adsorption sites, and the interface pathway proceeded with hydrogen spillover is found to be the prevailing process, which includes a high adsorption energy of -1.859 eV and an energy barrier of 0.885 eV. The density functional theory (DFT) calculation results are verified through experimental measurements including electrical conductivity relaxation and temperature programmed desorption. The contribution of interface reaction to the total hydrogen oxidation reaction reaches up to 98%, and the formation of Ni-ceria interface by infiltrating Ni to porous ceria improves the electrochemical activity by 72 % at 800 C.